A systematic scoping review of athlete mental health within competitive sport: interventions, recommendations, and policy - Prior, E.; Papathomas, A.; Rhind, D. (International Review of Sport and Exercise Psychology, 2022)
This systematic scoping review synthesises and appraises applied interventions, consensus/position statements, and grey literature regarding strategies to support athlete mental health and draws necessary connections across these documents. This review is informed by the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines (Moher et al., 2009). SPORTDiscus, PsycArticles, PsycINFO and SCOPUS were used to identify documents, alongside a search of all UK-based Olympic sport governing body websites. Thirty-seven documents met the review criteria. There were twenty-two intervention studies (including four case studies), nine position or consensus statements, and six grey literature documents (e.g. athlete mental health policies). Most interventions resulted in moderate or non-significant findings. Although position/consensus statements provide recommendations, they lack detail and primarily address research and organisational strategy rather than applied practice. Some grey literature recommendations are coherent with previous research, however, there are a lack of mental health policies produced by national governing bodies within elite sport. This review provides a comprehensive overview of athlete mental health literature and draws necessary connections across these different types of documents. Interventions with improved methodology (e.g. larger sample sizes), and more detailed recommendations within grey literature are required to inform applied efforts, recommendations, and future research.